Numerical and experimental study of ion energy distribution function in a dual-frequency capacitively coupled oxygen discharge - Luo, Han; Kenney, Jason; Rauf, Shahid; Korolov, Ihor; Schulze, Julian (Plasma Sources Science and Technology, 2023)
The plasma dynamics of a low pressure oxygen capacitively coupled plasma driven by dual frequencies (27.12 MHz and 271.2 kHz) is studied experimentally and numerically in this work. A retarding field energy analyzer system is employed in the experiment to measure the ion energy distribution function (IEDF) at the grounded electrode for different combinations of low-frequency voltages and pressures. One-dimensional particle-in-cell simulations of the oxygen plasma are conducted at the experimental conditions. A typical bimodal IEDF is observed and good agreement is obtained between experiments and simulations. A semi-analytical model based on the Child law sheath and fitted sheath voltage is constructed to study the structure of the IEDF. It is found that for the investigated conditions the low-energy peak of the IEDF is independent of the low frequency (LF) voltage but determined by the minimum sheath voltage during the sheath collapse; the energy spread of IEDF scales linearly with the LF voltage; both an increase of LF voltage and pressure create more low-energy ions.